Tax Amnesty Sebagai Moderator Pengaruh Perceived Behavioral Control Terhadap Wajib Pajak - Yusuf, Muhammad; Menne, Firman; Yusuf, Yulia Yunita (INOVATOR, 2020)
This study aims to examine and prove empirically: The role of tax amnesty as a moderator of the influence of perceived behavioral control on tax compliance. The focus of this research is whether tax amnesty can moderate perceived behavioral control towards increasing taxpayer compliance. The unit of analysis of this study is the corporate taxpayers at the North Makassar Pratama Tax Office who are participating in the tax amnesty program with a population of 610 taxpayers. Research respondents represented a sample of 90 corporate taxpayers. Determination of the sample using purposive sampling technique. The analytical method developed in this study is multiple regression analysis. The results showed that there was a positive and significant role of tax amnesty as a moderator on the effect of perceived behavioral control on tax compliance. This result also provides a clue that tax amnesty has a positive and significant influence in increasing taxpayer compliance.